Direct Human Contact with Siloxanes (Silicones) – Safety or Risk Part 1. Characteristics of Siloxanes (Silicones) - Mojsiewicz-Pieńkowska, Krystyna; Jamrógiewicz, Marzena; Szymkowska, Katarzyna; Krenczkowska, Dominika (Frontiers in Pharmacology, 2016)
Siloxanes are commonly known as silicones. They belong to the organosilicon compounds and are exclusively obtained by synthesis. Their chemical structure determines a range of physicochemical properties which were recognized as unique. Due to the susceptibility to chemical modifications, ability to create short, long or complex polymer particles, siloxanes found an application in many areas of human life. Siloxanes differ in particle size, molecular weight, shape and chemical groups. As a result, this determines the different physico-chemical properties, that directly affect the safety or the risk of their use. The areas that can be a source of danger to human health will be commented in this paper.